Jane Eyre - Bronte, Charlotte, 1816-1855; Leavis, Q. D. (Queenie Dorothy) (Harmondsworth Penguin Books, 1966)
Jane takes the job of governess and falls in love with the master of the house. The existence of his insane wife forces her to leave. The estate burns down leaving the man blind and his insane wife dead. Jane returns to care for him.
1
1